Human Cardiac Mesenchymal Stromal Cells From Right and Left Ventricles Display Differences in Number, Function, and Transcriptomic Profile - Stadiotti, Ilaria; Piacentini, Luca; Vavassori, Chiara; Chiesa, Mattia; Scopece, Alessandro; Guarino, Anna; Micheli, Barbara; Polvani, Gianluca; Colombo, Gualtiero Ivanoe; Pompilio, Giulio; Sommariva, Elena (Frontiers in Physiology, 2020)
Background. Left (LV) and right ventricles (RV) are characterized by well-known physiological differences, mainly related to their different embryological origin, hemodynamic environment, function, structure as well as cellular composition. Nevertheless, scarce information is available about cellular peculiarities between left and right ventricular chambers in physiological and in pathological contexts. Cardiac mesenchymal stromal cells (C-MSC) are key cells affecting many functions of the heart. Differential features that distinguish LV from RV C-MSC are still under-appreciated. Aim. To analyze the physiological differential amount, function and transcriptome of human C-MSC in LV vs. RV. Methods. Human cardiac specimens of LV and RV from healthy donors were used for tissue analysis of C-MSC number, and for C-MSC isolation. Paired LV and RV C-MSC were compared as for surface marker expression, cell proliferation/death ratio, migration, differentiation capabilities and transcriptome profile. Results. Histological analysis showed a greater percentage of C-MSC in RV vs. LV tissue. Moreover, a higher C-MSC amount was obtained from RV than from LV after isolation procedures. LV and RV C-MSC are characterized by a similar proportion of surface markers. Functional studies revealed comparable cell growth curves in cells from both ventricles. Conversely, LV C-MSC displayed a higher apoptosis rate and RV C-MSC were characterized by a higher migration speed and collagen deposition. Consistently, transcriptome analysis showed that genes related to apoptosis regulation or extracellular matrix organization and integrins were over-expressed in LV and RV, respectively. Besides, we revealed additional pathways specifically associated with LV or RV C-MSC, including energy metabolism, inflammatory response, cardiac conduction, and pluripotency. Conclusion. Taken together, these results contribute to the functional characterization of RV and LV C-MSC in physiological conditions. This information suggests a possible differential role of the stromal compartment in chamber-specific pathologic scenarios.